2009
DOI: 10.1002/stem.121
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Growth Arrest in Mesenchymal Stem Cells Is Bypassed by Wip1-Mediated Downregulation of Intrinsic Stress Signaling Pathways

Abstract: Human mesenchymal stem cells (hMSCs) have been widely studied as a source of primary adult stem cells for cell therapy because of their multidifferentiation potential; however, the growth arrest (also known as ''premature senescence'') often found in hMSCs cultured in vitro has been a major obstacle to the in-depth characterization of these cells. In addition, the inability to maintain constant cell growth hampers the development of additional genetic modifications aimed at achieving desired levels of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 67 publications
2
71
0
Order By: Relevance
“…Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) was performed with Power SYBR Ò Green PCR Master Mix (4367659; Applied Biosystems, Foster City, CA) on a MyiQ Single Color RealTime PCR Detection System (Bio-Rad, Hercules, CA) using the following primer sets: CD105, 5¢-GCCAGCATTG TCT CACTTCA TG-3¢ and 5¢-GCAACAAGCT CTTTCTTTAG TACCA-3¢; CD90, TCAGGAAATG GCTTTTCCCA and TCCTCAATGA GATGCCATAA GCT; CD73, CGCAA CAATG GCACAATTAC and CAGGTTTTCG GGAAA GATCA; PPARg, GCAGTGGGGA TGTCTCATAA TGC and CAGGGGGGTG ATGTGTTTGA A; alkaline phosphatase (ALP), GGACATGCAG TACGAGCTGA and TGTCTTCCGA GGAGGTCAAG; osteocalcin (OC), CAC TCCTCGC CCTATTGGC and CCCTCCTGCT TGGACA CAAA G; collagen type 1 alpha 1 (Col1a1), TAGGGTC TAG ACATGTTCAG CTTTGT and CCGTTCTGTA CGCAGGTGAT T; p16, GCCTTTTCAC TGTGTTGGAG and TGCCATTTGC TAGCAGTGTG [22]; p21, ACTT CGCCTG GGAGCGTGTG and CGTTTGGAGT GGTA GAAATC TGTCAT; p27, CGGCTAACTC TGAGGAC ACG C and ATTTGGGGAA CCGTCTGAAA CATT [23]; and GAPDH, GAAGGTGAAG GTCGGAGTC and GAA GATGGTG ATGGGATTTC. The thermal cycling conditions consisted of an initial denaturation step at 95°C for 5 min, then 50 cycles at 95°C for 30 s, 60°C for 30 s, and 72°C for 30 s, followed by a final extension step at 72°C for 10 min.…”
Section: Quantitative Real-time Reverse Transcriptionpolymerase Chainmentioning
confidence: 99%
“…Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) was performed with Power SYBR Ò Green PCR Master Mix (4367659; Applied Biosystems, Foster City, CA) on a MyiQ Single Color RealTime PCR Detection System (Bio-Rad, Hercules, CA) using the following primer sets: CD105, 5¢-GCCAGCATTG TCT CACTTCA TG-3¢ and 5¢-GCAACAAGCT CTTTCTTTAG TACCA-3¢; CD90, TCAGGAAATG GCTTTTCCCA and TCCTCAATGA GATGCCATAA GCT; CD73, CGCAA CAATG GCACAATTAC and CAGGTTTTCG GGAAA GATCA; PPARg, GCAGTGGGGA TGTCTCATAA TGC and CAGGGGGGTG ATGTGTTTGA A; alkaline phosphatase (ALP), GGACATGCAG TACGAGCTGA and TGTCTTCCGA GGAGGTCAAG; osteocalcin (OC), CAC TCCTCGC CCTATTGGC and CCCTCCTGCT TGGACA CAAA G; collagen type 1 alpha 1 (Col1a1), TAGGGTC TAG ACATGTTCAG CTTTGT and CCGTTCTGTA CGCAGGTGAT T; p16, GCCTTTTCAC TGTGTTGGAG and TGCCATTTGC TAGCAGTGTG [22]; p21, ACTT CGCCTG GGAGCGTGTG and CGTTTGGAGT GGTA GAAATC TGTCAT; p27, CGGCTAACTC TGAGGAC ACG C and ATTTGGGGAA CCGTCTGAAA CATT [23]; and GAPDH, GAAGGTGAAG GTCGGAGTC and GAA GATGGTG ATGGGATTTC. The thermal cycling conditions consisted of an initial denaturation step at 95°C for 5 min, then 50 cycles at 95°C for 30 s, 60°C for 30 s, and 72°C for 30 s, followed by a final extension step at 72°C for 10 min.…”
Section: Quantitative Real-time Reverse Transcriptionpolymerase Chainmentioning
confidence: 99%
“…However, ex vivo expansion to satisfy the immense cell numbers required for clinical use often results in senescence (27,31). We found that PDMCs, a population of multilineage MSCs derived from fetal placental tissue, are far more proliferative in vitro than adult BM-MSCs.…”
Section: Discussionmentioning
confidence: 91%
“…Many reports have shown that ROS accumulate in senescence cells and accompany cell cycle arrest (27). We therefore first analyzed the ROS levels of L-PDMCs by staining for 2¢,7¢-dichlorodihydrofluorescein diacetate (DCF-DA), which detects hydrogen peroxide (H 2 O 2 ) and superoxide anion levels, and hydroethidine (HE), which stains for superoxide anion.…”
mentioning
confidence: 99%
“…In fact, although normal senescent cells arrest with a G 1 DNA content, premature senescent tumor cells characteristically arrest in the G 2 phase of the cell cycle (29), likely due to defective G 1 checkpoint of cancer cells (43). Accordingly, it has been shown that introduction of Wip1 in normal human mesenchymal stem cells (G 1 arrested) allows bypass of senescence and extends cellular life span (44).…”
Section: Discussionmentioning
confidence: 99%